Sensory preservation in neck dissection: outcomes of a sub-sternocleidomastoid approach. (3rd August 2018) - Honda, Keigo; Asato, Ryo; Tsuji, Jun; Miyazaki, Masakazu; Kada, Shinpei; Kataoka, Yukiko; Taura, Akiko; Morita, Mami
Abstract: Objective: Cutaneous anesthesia in early postoperative period is common after neck dissection even if the cervical nerve (CN) rootlets are preserved. The aim of this study was to evaluate if the preservation of the terminal branches of CNs using sub-sternocleidomastoid (SCM) approach combined with medially placed skin incision can prevent early postoperative anesthesia. Material and methods: A retrospective chart review was performed on 129 neck dissections in 87 head and neck cancer patients. Results: The early postoperative sensory preservation rates for the ear tab, submandibular, lateral neck, and sub-clavicular areas of CN rootlet-preserved necks ( n = 86) were 75.6%, 20.9%, 74.4%, and 86.0%, respectively, compared with 37.2%, 2.3%, 2.3%, and 4.7%, respectively, in CN rootlet-resected necks ( n = 43). In CN rootlet-preserved necks, the sub-SCM approach ( n = 54) showed 81.5%, 27.8%, 92.6%, and 94.4% preservation rates, respectively, compared with 65.6%, 9.4%, 43.8%, and 71.9%, respectively, using the conventional subplatysmal approach ( n = 32). The rates were significantly better in the submandibular, lateral neck, and sub-clavicular areas after sub-SCM approach. Conclusions: Preservation of CN rootlets is a required element for sensory preservation in neck dissection. The sub-SCM approach can effectively prevent early postoperative cutaneous anesthesia following CN-preserving neck dissection.